A General Route to Metal‐Substituted Dipnictenes of the Type [L(X)M]2E21. Issue 13 (1st February 2018) - Tuscher, Lars; Helling, Christoph; Wölper, Christoph; Frank, Walter; Nizovtsev, Anton S.; Schulz, Stephan
Abstract: Two equivalents of LGa (L=HC[C(Me)N(2, 6‐ i Pr2 C6 H3 )]2 ) reacted with PX3 (X=Cl, Br) with insertion into two P−X bonds and formation of [L(X)Ga]2 PX (X=Cl1, Br2 ), whereas the analogous reaction with AsCl3 occurred with twofold insertion and subsequent elimination of LGaCl2 and formation of the Ga‐substituted diarsene [L(Cl)Ga]2 As2 (3 ). Analogous findings were observed in the reactions with Me2 NAsCl2, yielding the unsymmetrically‐substituted diarsene [L(Cl)Ga]As=As[Ga(NMe2 )L] (4 ). The reaction of As(NMe2 )3 with LGa gave [L(Me2 N)Ga]2 As2 (5 ) after heating at 165 °C for five days, whereas the reaction with LAl gave [L(Me2 N)Al]2 As2 (6 ) after heating at only 80 °C for one day. Finally, two equivalents of LGa reacted with Bi(NEt2 )3 to give [L(Et2 N)Ga]2 Bi2 (7 ). Complexes1 –7 were characterized by NMR spectroscopy ( 1 H, 13 C, 31 P), elemental analysis, and single‐crystal X‐ray diffraction (except for1 and5 ). The bonding situations in4, 6, and7 were analyzed by quantum chemical calculations. Abstract : Complex chemistry : LGa reacted with PX3 with formation of [L(X)Ga]2 PX (X=Cl, Br; L=HC[C(Me)N(2, 6‐ i Pr2 C6 H3 )]2 ), whereas reactions with AsCl3, Me2 NAsCl2, As(NMe2 )3, and Bi(NEt2 )3 yielded Ga‐substituted dipnictenes [L(Cl)Ga]2 As2, [L(Cl)Ga]As2 [Ga(NMe2 )L], [L(Me2 N)Ga]2 As2, and [L(Et2 N)Ga]2 Bi2 . Quantum chemical calculations revealed the bonding situation within the complexes.